In-Vivo Assessment of Shift in Plaque Ph Resulting from Pediatric Syrups for Duration of One Hour - Dr. Rodda Rajashekhar; Dr. Niharika Sowki; Dr. Ananya Kothe; Dr. Omkar Shetty; Dr. Gayathri G; Dr. Fazil Arshad Nasyam (The Bioscan, 2025)
Aim: To evaluate the pH shift of dental plaque following mouth rinse with the frequently recommended pediatric syrups. Materials and Methods: Forty participants were selected of age groups 12-14 years and categorized into 4 groups of 10 each based on usually used pediatric syrups. Oral prophylaxis was done to all the participants. After measuring the baseline resting plaque pH on test day, individuals were instructed to rinse with five milliliters of the pediatric syrup samples, swish around the mouth cavity for ten seconds, and then spits out. Samples of supragingival plaque were taken using the harvesting method at baseline and five, ten, fifteen, thirty, forty-five, and sixty minutes after rinsing with each medication. Plaque's pH was measured with a digital pH meter. One-way ANOVA and Tukey's post hoc test were used to statistically assess the collected data. Results: Mean pH of the pediatric syrups resulting in acidic pH in all the samples having highest acidic pH in Ibugesic. Ibugesic demonstrated the greatest decrease in plaque pH of any pediatric syrup in 5 minutes. Within 60 minutes, the pH gradually returned to near normal. Conclusions: All healthcare practitioners should be concerned with lowering the cariogenic risk of pediatric syrups.